Elementos centrales de experiencias educativas con enfoque STEM - Ramos-Lizcano, Corina; Ángel-Uribe, Isabel-Cristina; López-Molina, Giovanni; Cano-Ruiz, Yuly-Marcela (Revista Científica, 2022)
This article presents a bibliographic review in multidisciplinary databases to identify central elements in the development of STEM educational experiences from various meanings such as STEM+A or STEAM, for their integration with the arts; STEM+H, for humanities or STEM+Agriculture; among others. This approach has increased its presence at various educational levels, partly due to promotion through multilateral organizations such as the OECD and the IDB, and by the definition of public policies, especially in North America. 67 research articles were analyzed, out of which 53 were selected as a sample because they account for STEM experiences developed in 19 countries on four continents. The majority (54.72%) relate experiences from North America, especially the United States, which contributes with 47.17% of the total sources in the study. The review identifies the following trends: learning purposes, which focus on the development of skills; collaboration between groups and generating good practices for lifelong learning; the use of active learning strategies; the role of ICTs, which are identified as articulators on the basis of their didactic role; and, the success factors of the approach, in which the role of a teacher that prioritizes learning is preponderant. From these experiences, it is concluded that the role of the teacher in the execution of learning experiences with a STEM approach is fundamental, given the pedagogical, didactic, and human implications of developing it.